Impelementasi Kebijakan E-Faktur Dalam Meningkatkan Kepatuhan Pengusaha Kena Pajak Di Kantor Pelayanan Pajak Pratama Jakarta Kelapa Gading 2021-2023 - Prasetyo, Sisman; Julito, Kiko Armenita; Khoiri, Khoiri (Jurnal Akuntansi Manajerial, 2024)
This study aims to determine the effect of profitability, liquidity, and taxes on capital structure in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2020-2022. The dependent variable used in this study is Capital Structure, while the independent variables used are profitability, liquidity, and taxes. This study uses a quantitative approach with a research population in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2020-2022. The sampling technique used is purposive sampling with a total sample of 51 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange as a research sample. The data source used is secondary data in the form of financial reports of manufacturing companies listed on the IDX for the period 2020-2022 which can be obtained through the website www.idx.com. The results of this study indicate that simultaneously profitability, liquidity and tax variables affect the capital structure of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2020-2022. While partially shows that: (1) Profitability (ROA) has no effect on capital structure (2) Liquidity (CR) has a negative and significant effect on capital structure, (3) Tax has no effect on capital structure.